تحليلية لوضع توفير الطاقةPSM في شبكات Ad-hoc - Hijazieh, Mohammed; Sultanah, Mais (Latakia University Journal -Engineering Sciences Series, 2019)
دراسة تحليلية لوضع توفير الطاقةPSM في شبكات Ad-hoc محمد حجازية ميس سلطانة تعتبر مسألة زيادة استهلاك الطاقة للعقد الجوالة في الشبكات المحلية اللاسلكية WLANs من أهم التحديات التي تواجه شبكات Ad-hoc نظرا لمحدودية سعات مصادر الطاقة المستخدمة في هذه الأجهزة الإلكترونية الجوالة , حيث إن انخفاض طاقة العقد الجوالة يؤثر على نشاطات التواصل بين هذه العقد ضمن الشبكة اللاسلكية. يعد وضع توفير الطاقة PSM المستخدم في معيار IEEE802.11 واحدا من أكثر التقنيات شعبية في الشبكات المحلية اللاسلكية والذي ينسق حالات الطاقة المختلفة للأجهزة اللاسلكية المتصلة بحيث يمكن العقد الجوالة من الدخول في حالة الخمول Doze معظم الوقت ولا تعود هذه العقد لحالة النشاط إلا خلال فترات زمنية محددة وبشكل دوري عند كل بداية لنافذة رسائل إعلان إشارات المرور.ATIM تم في هذه البحث تقديم دراسة عن وضع توفير الطاقة وتحدياته في شبكات ad-hoc بالإضافة إلى تقديم دراسة تحليلية ملخصة عن كيفية تحسين وضع توفير الطاقة في معيار IEEE802.11 في حالات مختلفة لحمل الشبكة. The issue of increasing the power consumption of mobile nodes in Wireless Local Area Networks WLANs is one of the most important challenges facing Ad-Hoc networks due to the limited capacity of energy sources used in these mobile devices, as the low power of the mobile nodes affects the communication activities of these nodes within the wireless network. The power saving mode PSM used in the IEEE802.11 standard is one of the most popular techniques in the wireless LAN, which coordinates the different power situations of connected wireless devices so that the mobile nodes can enter into doze status most of the time and they don’t return to the activity status except during specific intervals and periodically at each start of announcement traffic indication messages window ATIM. I this paper, a study of power saving mode and its challenges were provided in ad-hoc networks as well as a brief analytical study was provided on how to improve the power saving mode in IEEE802.11 in different situations of network load.